Performance insights into spray-dryer microencapsulated Bacillus thuringiensis cry pesticidal proteins with gum arabic and maltodextrin for effective pest control - de Oliveira, Jhones Luiz [UNESP]; Gómez, Isabel; Sánchez, Jorge; Soberón, Mario; Polanczyk, Ricardo Antonio [UNESP]; Bravo, Alejandra (Springer Nature, 2024)
Abstract: Bacillus thuringiensis (Bt) produces crystals composed mainly of Cry pesticidal proteins with insecticidal activity against pests but are highly susceptible to degradation by abiotic factors. In this sense, encapsulation techniques are designed to improve their performance and lifetime. However, the effects of polymeric matrix encapsulation such as gum arabic and maltodextrin by spray-dryer in the mechanisms of action of Bt kurstaki and Bt aizawai are unknown. We analyzed crystal solubilization, protoxin activation, and receptor binding after microencapsulation and compared them with commercial non-encapsulated products. Microencapsulation did not alter protein crystal solubilization, providing 130 kDa (Cry1 protoxin) and 70 kDa (Cry2 protoxin). Activation with trypsin, chymotrypsin, and larval midgut juice was analyzed, showing that this step is highly efficient, and the protoxins were cleaved producing similar ~ 55 to 65 kDa activated proteins for both formulations. Binding assays with brush border membrane vesicles of Manduca sexta and Spodoptera frugiperda larvae provided a similar binding for both formulations. LC50 bioassays showed no significant differences between treatments but the microencapsulated treatment provided higher mortality against S. frugiperda when subjected to UV radiation. Microencapsulation did not affect the mechanism of action of Cry pesticidal proteins while enhancing protection against UV radiation. These data will contribute to the development of more efficient Bt biopesticide formulations. Key points: • Microencapsulation did not affect the mechanisms of action of Cry pesticidal proteins produced by Bt. • Microencapsulation provided protection against UV radiation for Bt-based biopesticides. • The study’s findings can contribute to the development of more efficient Bt biopesticide formulations. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Bacillus thuringiensis; Manduca sexta; Mechanism of action; Microencapsulation; Spodoptera frugiperda